Effect of orthopneic position and pursed-lip breathing on dyspnea in patients with chronic obstructive pulmonary disease - Arifuddin, Arifuddin; Rayasari, Fitrian; Anggraini, Dewi; Jumaiyah, Wati (School of Health Sciences Al-Ma'arif, 2026)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation and dyspnea that significantly reduces patients’ functional capacity and quality of life. Non-pharmacological nursing interventions, including breathing techniques and therapeutic positioning, have increasingly been applied to improve respiratory function and alleviate dyspnea symptoms. However, evidence regarding the combined effectiveness of orthopneic positioning and pursed-lip breathing in clinical inpatient settings remains limited. Objective: This study aimed to evaluate the effect of orthopneic position combined with pursed-lip breathing on dyspnea indicators, including respiratory rate, oxygen saturation, and peak expiratory flow, among patients with chronic obstructive pulmonary disease. Methods: A pre-experimental one-group pretest–posttest design was conducted in the MDR Baji Ati ward, Labuang Baji General Hospital Makassar. Seventeen hospitalized adult COPD patients meeting inclusion criteria participated in the study. The intervention consisted of orthopneic positioning combined with pursed-lip breathing exercises administered for 20–30 minutes per session, at least three times weekly for four weeks. Outcome measures included respiratory rate, oxygen saturation, and peak expiratory flow assessed before and after the intervention. Data were analyzed using paired t-test with a significance level of 0.05. Results: The intervention significantly reduced respiratory rate from 23.4 to 18.9 breaths per minute (p = 0.001), increased oxygen saturation from 89.6% to 96.4% (p = 0.001), and improved peak expiratory flow from 256 L/min to 367 L/min (p = 0.001). Large effect sizes across outcomes indicated substantial clinical improvement. No adverse events were reported during the intervention period. Conclusion: The combined application of orthopneic positioning and pursed-lip breathing effectively improved respiratory parameters and reduced dyspnea among COPD patients. This evidence-based nursing intervention represents a safe, feasible, and clinically valuable strategy for respiratory symptom management in hospitalized patients with chronic obstructive pulmonary disease.